2020
DOI: 10.1177/0743558420967117
|View full text |Cite
|
Sign up to set email alerts
|

In-Between: Late-Arriving Teens in Adult Education Programs Navigating Child and Adult Immigrant Narratives

Abstract: We report on a grounded theory study of late-arriving immigrant youth (LIY) who arrived in the United States at 16–18 years of age and were referred to daytime General Education Diploma (D-GED) programs. These programs provide an alternate path to a high school diploma for youth with insufficient knowledge of English to complete graduation requirements before turning 19 years. Based on interviews with 38 youth from Latin America, we propose the core category of our grounded theory to be students Navigating Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…While individual therapy may be an important resource, such a focus detracts from viewing migration of unaccompanied youth as a global problem confronted by individuals as well as their sending and receiving communities and institutions such as schools, social service agencies, and placement programs. We believe that to provide a nuanced narrative of the youth’s experience, an integrative synthesis of the research literature is needed that takes a resilience-oriented and ecological perspective that understands these youth as “in-between” childhood and adulthood (Birman et al, 2020).…”
Section: Unaccompanied Youth Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…While individual therapy may be an important resource, such a focus detracts from viewing migration of unaccompanied youth as a global problem confronted by individuals as well as their sending and receiving communities and institutions such as schools, social service agencies, and placement programs. We believe that to provide a nuanced narrative of the youth’s experience, an integrative synthesis of the research literature is needed that takes a resilience-oriented and ecological perspective that understands these youth as “in-between” childhood and adulthood (Birman et al, 2020).…”
Section: Unaccompanied Youth Migrationmentioning
confidence: 99%
“…This status, in turn, has many implications for their experience, including the level of care they receive upon resettlement, types of placements, and even schooling opportunities. However, different legal systems and resettlement programs they encounter may not recognize and address their “in-betweenness” but treat them as either children or adults (Birman et al, 2020). Therefore, we consider the implications of this for the ways researchers have approached the study of this group.…”
Section: Unaccompanied Youth Migrationmentioning
confidence: 99%
“…Adult higher education generally consists of three main forms: adult higher education in general institutions of higher learning, education in independent adult colleges and universities, and self-study examinations for higher education. Among them, according to the explanation of Adult Education Association, "Adult education in general institutions of higher education refers to a kind of purposeful, planned, organized and specialized educational activities implemented by general institutions of higher education for adults on the basis of secondary education in various ways and means" [1][2]. Nowadays, more than one general college and universities across the country have different levels or types of adult education, and general colleges and universities have made important contributions to the process of establishing and perfecting China's adult higher education system [3].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in our study of recent accompanied LIY in Miami, Florida, we found that the youth had intentionally migrated before turning 18 because coming as minors made it possible for them to accompany or join their parents as dependent children (Birman et al, in press). They also believed that because they were not legally adults, they were young enough to enter a U.S. high school and build a future they wanted.…”
mentioning
confidence: 97%
“…Unlike immigrant teens who arrived when they were younger, LIY must adapt to the new country and to school while going through typical challenges that come with the developmental transition to adulthood. They arrive in the United States at an educational disadvantage to their nonimmigrant peers, facing barriers resulting from not knowing English, and the need to acculturate to a new country (Birman et al, in press; Ruiz de Velasco & Fix, 2000). Research suggests they are susceptible to dropping out of school (Joint Conference on Standard Setting for Large-scale Assessments, United States.…”
mentioning
confidence: 99%